Imported crime. Exploring the links between European immigration and crime in Revista de Policía (Buenos Aires, 1897-1916) (Delito y Sociedad, 2020)
Framed in my doctoral thesis, in this article I describe some of the ways in which the links between European immigration and crime were conceptualized, based on the analysis of a periodic publication edited by the Policía de la Capital, Revista de Policía. The theoretical-methodological strategy selected to address the issue was the Grounded theory, pioneered by Barney Glaser and Anselm Strauss in the 1960s. More  articularly, I present the categories and labels that became central in the analysis carried out, by means of the constant comparative method, on Revista de Policía, published between the end of the 19th century and the beginning of the 20th: «asociación estadística entre inmigración y delincuencia», «anarquistas» and «inmigrantes peligrosos». In the same direction, I describe police statistics and two theoretical elements of positivist criminology (the dangerousness and «medicalization» of criminology) as knowledge that they were called upon to sustain such links between immigration and crime.
Keywords: categories; European immigration; crime; police; knowledge